Antibody Responses toward the Major Antigenic Sites of Influenza B Virus Hemagglutinin in Mice, Ferrets, and Humans - Sun, Weina; Kang, Davina S.; Zheng, Allen; Liu, Sean T. H.; Broecker, Felix; Simon, Viviana; Krammer, Florian; Palese, Peter (Journal of virology, 2019)
This study dissected the specific antibody responses toward the major antigenic sites and the noncanonical epitopes of influenza B virus hemagglutinin in animals and humans using novel reagents. These findings will guide the design of the next generation of influenza virus vaccines. The influenza B virus hemagglutinin contains four major antigenic sites (the 120 loop, the 150 loop, the 160 loop, and the 190 helix) within the head domain. These immunodominant antigenic sites are the main targets of neutralizing antibodies and are subject to antigenic drift. Yet little is known about the specific antibody responses toward each site in terms of antibody prevalence and hemagglutination inhibition activity. In this study, we used modified hemagglutinins of influenza B virus which display only one or none of the major antigenic sites to measure antibody responses toward the classical as well as the noncanonical epitopes in mice, ferrets, and humans. With our novel reagents, we found that both hemagglutination inhibition antibodies and total IgGs were mostly induced by the major antigenic sites. However, in human adults, we observed high hemagglutination inhibition antibody responses toward the noncanonical epitopes. By stratifying the human samples into age groups, we found that the noncanonical antibody responses appeared to increase with age. IMPORTANCE This study dissected the specific antibody responses toward the major antigenic sites and the noncanonical epitopes of influenza B virus hemagglutinin in animals and humans using novel reagents. These findings will guide the design of the next generation of influenza virus vaccines.